(untitled) (Вісник Київського національного університету імені Тараса Шевченка. Хімія, 2014)
Dependence between structures of R-oxyflavones and their spectral and basic properties has been investigated. It was found that pKa of flavones, depending on positions of hydroxy and methoxy groups, increase by 6-8 orders of magnitude upon excitation and reaches 3.7-6.6 units. Due to high pKa* value carbonyl group can serve as a proton acceptor in the excited-state intramolecular proton transfer as well as in the formation of phototautomers of 7- and 4’-hydroxyflavones in protic solvents.